Strategies of Virtual Influencers Crafting Viral Content in Indonesia - Zenobia, Zhafira; Christin, Maylanny (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
Virtual influencers are becoming increasingly popular on social media, with many major brands targeting young consumers preferring virtual influencers as they are easier to manage compared to human influencers. This study aims to analyze the digital storytelling strategies and representations of virtual influencers from various countries, specifically Indonesia, the United States, and Brazil, on social media platforms like TikTok. Using a qualitative method with narrative analysis, this study found that virtual influencers reflect significant cultural and market differences based on their promotional focus and content style. For instance, Indonesian virtual influencer Arbie Seo promotes products from the brand Nabati, and Lentari Pagi focuses on promoting sports events like e-football. Meanwhile, American virtual influencer Lil Miquela collaborates with major brands like Dior, and Lu do Magalu from Brazil promotes household products. Digital storytelling is compelling as it unconsciously draws audiences into following storylines by integrating multimedia elements presented by virtual influencer content. This strategy not only enhances audience engagement but also increases the potential for content to go viral. This study provides insights into how virtual influencers build audience connections through storytelling and appealing representations.